Preliminary study of the atmospheric pollen in "Sierra de las Nieves" Natural Park (Southern Spain) - Picornell Rodríguez, Antonio; Recio-Criado, María Marta; Trigo-Pérez, María del Mar; Cabezudo-Artero, Baltasar (My University, 2018)
‘Sierra de las Nieves’ is a Natural Park and a Biosphere Reserve located in the south of Spain. This protected area has a high diversity of ecosystems with abundant endangered species which have led it to be in ways to become a National Park. Some of those species have anemophilous pollination strategies. Since 1991, the Aerobiology research team of the University of Malaga has been sampling and studying airborne pollen in different cities of Malaga province. Nevertheless, a pollen trap has never been installed inside a Natural Park for a continuous sampling process. The objectives of this study were to determinate the atmospheric pollen behaviour of the main taxa registered during winter and spring months in this protected area, as well as compare the results with the data obtained in urban stations during the same period searching for significant differences. The pollen samplings were made by means of a Hirst-type volumetric pollen trap inside the protected area of the Natural Park. The samples obtained were mounted and counted according to the methodology proposed by the Spanish Aerobiology Network (REA). The high vegetal diversity of ‘Sierra de las Nieves’ are reflected in the pollen counts. Significant differences between the sampligs obtained at ‘Sierra de las Nieves’, Malaga and the neraby city of Ronda stations were found regarding to the daily pollen concentration. The qualitative and quantitative differences can be explained by the different land use, altitude, climatic characteristics and by the distance between aerobiological stations and pollen emission sources. There is an important influence of wind dymanic and others meteorological factors.
Keywords: Microbiología del aire; Fenología; Polen; Naturaleza; Alergia; Parques Nacionales; Sierra de las Nieves; Espacios naturales protegidos; Especies endémicas; Native species